Jesus wept, robots can't. (23rd August 2021) - Gill, Sam
Abstract : Exploring the implications of the shortest of biblical verses 'Jesus wept' in contrast with the incapability of robots to weep or feel empathy and emotion as exemplified in the classic post-apocalyptic film Terminator 2, this essay argues that movement, gesture, body, experience and improvization are essential elements to any emerging valued world. Certainly religion, despite our strong association of it with the spiritual and the immaterial, does not and cannot exist, or even be imagined, apart from these distinctively human biological features. The study of religion must be, among other concerns, grounded in biology.